The Socio-Economic Dislocation of the Javanese Chinese Community during the Revolution: The Transformation from Citizens to Refugees - Aini, Nurul; Darini, Ririn; Al Hazar, Badrizal (Universitas Hamzanwadi, 2026)
The journey towards Indonesian independence not only fostered a spirit of nationalism but also revealed a dark side in the form of social suffering among the people. One of the forgotten tragedies was the displacement of ethnic Chinese communities in Java, who lost their homes, jobs, and sense of security amid the political turmoil of the revolutionary period. This study aims to explain the social and economic dislocation experienced by the Chinese community as part of a domestic humanitarian disaster. The approach used is a historical method with qualitative analysis based on archival sources, government reports, and contemporary documents. The results of the study show that the displacement was not merely the result of ethnic conflict, but a reflection of a power vacuum and widespread socio-economic tensions. Despite suffering great losses, the Chinese community was able to survive through internal solidarity, community assistance, and adaptation to the new post-war economic structure. This study confirms that the struggle for independence not only brought about political freedom but also left deep social wounds for Indonesian civilians, including those who had been an integral part of Javanese society. This research offers a new perspective by integrating colonial archival sources, visual data, and Karl Polanyi's disembedding theory to understand displacement as a form of domestic socio-economic disaster during the revolution, a theme that has not been widely discussed in Indonesian historiography.